Characterization of three agricultural production organizations in the sub-region Caraigres: Part 1. Descriptive analysis of agro supply chains - Vargas-Jarquín, Edgardo (2015)
This paper describes a study of agricultural production chains inherent in three rural organizations and the farmers’ characteristics that shape them. Also, it was possible to identify the different relationships that exist in the production environment between partners within their organizations, as well as the underlying network structures that occur in that domain. The studied organizations corresponded to Agricultural Producers Association of the cantons of Acosta and Aserrí (ASOPROAAA), The Association of Organic Families of Caraigres Hills (AFAORCA) and the Association of Beekeepers of the Caraigres Region (APICARAIGRES) all these located in the cantons of Acosta, Aserrí, Desamparados, León Cortés and Corralillo, to the south of San José, Costa Rica. In order to meet the objectives, the three organizations were characterized by applying descriptive parameters taking a number of variables into account. Among these variables, personal, production and financial characteristics were identified. A survey was conducted to all the associates of AFAORCA and APICARAIGRES and the same instrument to a sample of ASOPROAAA associates, according to their respective proportions. In this article, conditions inherent in the three agricultural organizations chains are described, as well as the main characteristics of the production units, such as size, production levels and product marketing. The results on the characteristics of farmers and the links that the social fabric and structure of these networks are formed are left for further publications